The Role of Entrepreneurial Self-Efficacy in Measuring the Entrepreneurial Motivation of Vocational High School Students in Lumajang Regency - Andrianto, Ahmad; Cipto Wardoyo; Satia Nur Maharani (International Journal of Business and Quality Research, 2025)
This study aims to analyze the influence of creative projects and entrepreneurial mindset on entrepreneurial motivation, considering the role of entrepreneurial self-efficacy as a mediating variable. This study uses a quantitative approach with a survey method through hypothesis testing. The sample for this study involved 156 vocational high school students in grade XII in Lumajang Regency. Data analysis was performed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of this study indicate that creative projects have a significant positive effect on entrepreneurial self-efficacy and entrepreneurial motivation. In addition, entrepreneurial mindset has a significant and positive effect on entrepreneurial self-efficacy, but does not have a significant and negative effect on entrepreneurial motivation. Self-efficacy plays an important role in this study in mediating the significant and positive effect of creative projects and entrepreneurial mindset on entrepreneurial motivation. Self-efficacy also has a significant and positive effect on the entrepreneurial motivation of vocational high school students in Lumajang Regency. The implications of this study can help vocational high school educational institutions in Lumajang Regency to improve their entrepreneurship programs by directing them towards the development of creative projects to realize entrepreneurial motivatio.